Faith in the gap – factors affecting faith formation in emerging adults during a one-year vocational intern programme - White, Pete (Practical theology, 2025)
Emerging adulthood is a time of transformation and the gap year, as a liminal space, increases potential for change. This article describes case study research into the effect of a one-year vocational intern programme on the formation of faith amongst a group of emerging adults. The research identified factors that contributed to the formation of faith, in the context of exploring vocation. These are drawn together in a model for practice based in a theology of vocation for similar programmes and potentially, for ministry in other contexts with this age group.